Disorders of the Neonatal Airway Fundamentals for Practice - Lioy, Janet; Sobol, Steven E. (Springer New York : Imprint: Springer, 2015)
Disorders of the Neonatal Airway serves as a comprehensive, multidisciplinary resource for all practitioners who care for neonates with airway disorders. With the evolution of advances in neonatology and neonatal airway care over the past three decades, the survival rate and life expectancy of premature newborns have dramatically increased to well over 50% in 24-25 week gestation infants.  Unfortunately, survival with long-term intubation has brought a corresponding increase in acquired airway disorders needing collaborative high level neonatal and otolaryngological care.  Additionally, with the advent of fetal therapy, congenital airway disorders now make up a substantial number of neonates with complex airway disorders.  Because of this fact, there has been increased focus on the multidisciplinary evaluation and management of neonatal airway disorders.  The book is organized into three sections: the first focuses on Malformations and Deformations, the second focuses on Assessment, Evaluation, and Treatment, and the third discusses Education, Simulation, and Quality. As one of the only comprehensive resources on the topic, Disorders of the Neonatal Airway focuses on a multidisciplinary approach to the neonatal airway.  This unique approach makes this reference a must read for practitioners from many disciplines.